Sistem Pakar Untuk Mendiagnosis Penyakit Kanker Payudara Menggunakan Metode Certainty Factor Berbasis Web - Monda, Karolinda; Mau, Sisilia D. B.; Sinlae, Alfry Aristo Jansen (Jurnal Teknik Informatika UNIKA Santo Thomas, 2022)
Information technology has been widely applied in the medical field to assist doctors in diagnosing cancer and also for patients to find out the extent of the disease. The number of patients with breast cancer at the Regional General Hospital, Prof. dr. W. Z. Yohannes in 2020 until November reached 77 patients. The still high number of breast cancer sufferers is the background for this research, with the aim of this expert system being able to help provide clear information for patients or the general public so that they can find out the symptoms they are experiencing early on. The method used in this study is the Certainty Factor (CF) method. The Certainty Factor method is a method to prove whether a fact is certain or uncertain and also describes the level of expert confidence in the problems at hand. The application is designed using the PHP programming language and MySQL database, and the methodology used in this research is the Expert System Life Cycle (ESLC) method. The result of this research is an expert system application for diagnosing breast cancer that can help the general public in diagnosing breast cancer, especially helping patients get information to consult quickly about symptoms and diseases of breast cancer.